New species of Mouse Spiders (Araneae: Mygalomorphae: Actinopodidae: Missulena) from the Pilbara region, Western Australia - Harms, Danilo; Framenau, Volker W. (Zootaxa, 2013)
Two new species of Mouse Spiders, genus Missulena, from the Pilbara region in Western Australia are described based on morphological features of males. Missulena faulderi sp. nov. and Missulena langlandsi sp. nov. are currently known from a small area in the southern Pilbara only. Mitochondrial cytochrome c oxidase subunit I (COI) sequence divergence failed in clearly delimiting species in Missulena, but provided a useful, independent line of evidence for taxonomic work in addition to morphology.